LINGUOCULTURAL FEATURES OF PAREMIA REPRESENTING INTERPERSONAL RELATIONSHIPS AND THEIR USAGE IN THE PROCESS OF THE LANGUAGE LEARNING - Daminova , Charos Zaydilla qizi (Innovative Development in Educational Activities, 2023)
In this article describes the similarities and differences between paremias in the different languages, proverbs that express the culture and mentality of nations, and express interpersonal relationships. Furthermore the article explains the ways of increasing the speaking skill by using paremias in the speech.